ردود أبي حيان في المرفوعات في (ارتشاف الضرب من لسان العرب) - مصطفى, أ.م.د.دانا أحمد; حسن, أ.م.د.كورديا أحمد (Sulaimani Journal for Humanities, 2023)
(Abu Hayyan) abbreviated his explanation of the facilitation called (appendix and complement in explaining the facilitation) and called the abbreviated (the resorption of the multiplication from the tongue of the Arabs). This book is full of grammatical opinions and linguistic sayings, and there are responses and explanations of ideas, comments and weightings, and he relied in many of his opinions on hearing.